Antibacterial Effects of Herbal Compounds against Acinetobacter baumannii Isolated from Hospital of Tehran, Iran - Hossein Saghi; Abbas Bahador; Ferdoes Amiri Dastjerdi; Hassan Asadolahi; Mehdi Neyshaboori; Esmaeili Mohammad; Meskini Maryam; Davoud Esmaeili (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2015)
Increasing isolation of multidrug-resistant Acinetobacter baumannii (MDR) has been reported in worldwide and it is recently one of the most difficult nosocomial acquired gram-negative pathogens to control and treatment. These bacteria are one of ESBL producing that great potential have for the rapid development of antibiotic resistance. Use of medicinal herbaceous drugs recommended for treatment since ancient periods. Humans have been used and realize their beneficial effects. With the increase in population and urban growth, reduced use of synthetic drugs, many of these of medicinal herbs have been replaced. Because of Satureja, Origanum vulgare and Thyme essence has antimicrobial properties so can be used against infections caused by MDR Acinetobacter baumannii. In this study the antimicrobial effects of Satureja, Origanum vulgare and Thyme essence on drug-resistant strains of Acinetobacter baumannii were investigated using antimicrobial analysis with CLSI 2013 and Kirby Bauer method. The agar dilution method results revealed that Satureja essence compare with Origanum vulgare and Thyme had strong inhibitory effects against Multidrugresistant strains of A. baumannii. Because of proper effects of plant essential oils, with a broader range of studies can be used as a complementary therapy.